Giuseppe Buroni’s Platonic-Rosminian Metaphysics - Buganza, Jacob (Razón y fe, 2025)
In this article, the author seeks to demonstrate that Giuseppe Buroni´s metaphysics, which can be called Platonic-Rosminian, expresses perennial Christian philosophy. Therefore, he collected Buroni’s central approaches from Nozioni di ontologia. Here, we can find an impressive metaphysical work about the ontological distinction, the matter of unity and multiplicity, the production or the creation from the point of view of theosophy, and the demonstration of God’s existence.